Development of a techno-economic analysis tool for anaerobic digestion in smallholder farming systems in the context of the water-energy-food nexus - Mossissa, Amsalu Tolessa (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.